Influence on information on negative nutrients on the buying habits of academic staff / Afeza Ahmad and Bakhtiar Abd Rani - Ahmad, Afeza; Abd Rani, Bakhtiar (2005)
In recent years consumers have become increasingly interested in nutritional issue. This interest in nutrittion is fuelled by a number of factor including life style, aging problem, gender dietary and health concern.